2016
DOI: 10.1111/aos.13097
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness after vitrectomy for epiretinal membrane combined with vitreomacular traction

Abstract: Choroidal thickness was greater in ERM eyes with than without VMT possibly due to direct anteroposterior traction on the retina and choroid, increased vascular endothelial growth factor associated with stress on retinal pigment epithelial cells and inflammation. After vitrectomy, mean SFCT reduced in the eyes with VMT, but not in those without VMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…Kang et al [20] in a recent work showed that, in patients affected by iERM without vitreomacular traction, CT remained unchanged from the baseline to 6 months after surgery. They postulated that ERM alone, which is associated with tangential traction without AP traction, may not affect CT [20] .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Kang et al [20] in a recent work showed that, in patients affected by iERM without vitreomacular traction, CT remained unchanged from the baseline to 6 months after surgery. They postulated that ERM alone, which is associated with tangential traction without AP traction, may not affect CT [20] .…”
Section: Discussionmentioning
confidence: 95%
“…They postulated that ERM alone, which is associated with tangential traction without AP traction, may not affect CT [20] . However, they did not report a baseline comparison with normal fellow eyes but only with eyes affected by iERM and AP traction that showed a significantly higher subfoveal CT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agrawal et al used the CVI as an effective follow-up tool to show the proportionate change in choroid vasculature as a more stable and consistent biomarker of disease progression (Michalewska et al 2015;Tan & Agrawal 2015;Agrawal et al 2016;Michalewska et al 2016). Although the pathogenesis of the ERM is not completely understood and different hypotheses have been postulated, Kang et al, speculate that vitreomacular traction could induce thickening of the choroid (Kang et al 2016). Additionally, in the VT-group, the CVI decreased gradually by a small quantum between the baseline and 3 months after vitrectomy with ERM removal and ILM peeling (Fig.…”
Section: Discussionmentioning
confidence: 99%